A Single Currency as a Remedy in the Eurozone’ Preparedness for the Economic Crisis and the Smooth Functioning of the Euro Area? - Sawa, Dawid (International Studies. Interdisciplinary Political and Cultural Journal, 2022)
The aim of this article is to present the situation and the financial condition of the euro area and to orientate itself towards the future. The eurozone crisis is the greatest challenge for the entire euro area but also for the European Union as such. Its bad financial situation and the related stagnation force us to reflect and take corrective measures. Failure to draw conclusions generates further problems and disintegrates the entire euro area.